Pranata Keluarga Muslim dalam Sistem Kekerabatan Parental Sunda - Harits, Iir Abdul (Jurnal Ilmu Dakwah, 2008)
Basically dakwah deals with the problem of society living about institution and culture. Itâs contalation in Sunda Societies become not simple. Itâs dilemma to Daâi lies between holding strongly about legality of patriarkhis fiqh norms with Sunda culture system was developed and aplicated in society, because it is loss or elimited basic anthropologis.